OP0245-PARE The emotional and information support needs of people living with polymyalgia rheumatica. (23rd January 2014) - Cumming, J.; Gilbert, K.
Abstract : Background: The number of enquiries from clients living with polymyalgia rheumatica [PMR] to two national helplines has increased. The emotional and information support needs of this group has yet to be explored using these original data sources. Objectives: To analyse the contact information relating to clients diagnosed with PMR collected by the helpline and websites over 2011 and compare results with those of the leading peer support group. Methods: Every anonymous contact by phone, email, letter and an online forum received in both helplines was logged onto secure confidential databases in line with the UK Data Protection Act. Where PMR was self reported this was collated and examined and results compared where possible between the two helplines. Results: The lgeneric, helpline received a total of 11, 526 contacts from people with a wide range of rheumatic and musculoskeletal diseases (RMDs), of which 308, [2.6%] identified themselves as living with PMR. This number is 20.5% higher than previous years. 40, 415 viewed the website's PMR pages. During 2011 the dedicated helpline took 503 calls of which approx. 85% identified themselves as having PMR. The following results for the generic helpline showed age ranges of people self reporting PMR fell broadly into those expected with 70 [32%] aged 45 to 64 and 144 [66%] over 65 years. The majority of contacts in the PMR group are from women [83%]. In the population of other RMD conditions this is only 75%. 17% of people living with PMR report they also contend with other RMD condition, the highest [11%] being osteoarthritis. Other co-morbidities are reported by 10%, the most common being osteoporosis for a third of these clients. A high percentage of contacts with PMR were affected physically, with 72% experiencing pain and nearly a third [95] needed emotional support and 6.8% said they felt low and depressed. 43% wanted medical information about pain relief and symptom control explained. 137 clients to the generic helpline required written information and this is included referral to the dedicated helpline. 93% of these received pain booklets, 78% PMR factsheets. In 2011 website data shows 3304 people downloaded PMR specific factsheets. Since the dedicated helpline has been listed on www.patient.co.uk, increasing numbers of GPs have been referring newly-diagnosed patients to the helpline. As a result, 98 information packs for PMR have been sent out. While newly-diagnosed patients report needing information about the illness and its treatment, callers to the helpline who have been diagnosed some time ago report problems of returned symptoms and new symptoms of pain and other side effects during the process of "tapering off" of the steroids. Conclusions: 1. Where we see 72% of people wanting to talk about their pain and 43% needing support about their medication then it is possible that uncontrolled pain is a huge concern for people living with PMR. To this is added anxiety about being on steroids for a long period. 2. The high numbers of people requiring detailed information, both from website and in print, about PMR may indicate that at diagnosis not enough information is given to the patient. 3. PMR is a highly unsettling and worrying condition, often accompanied by other co-morbidities, for many as is demonstrated by the high numbers of clients seeking one to one emotional counselling and peer support. Disclosure of Interest: None Declared